Cross cultural public relations and algorithmic transparency in AI-Driven fintech - Husada, Safaruddin; Yunus, Ulani; Chaidaroon, Suwichit Sean; Akbar, Nagiza (PRofesi Humas, 2026)
Background: The rapid adoption of Artificial Intelligence (AI) in the fintech industry has resulted in changes in organizational and management communication models, stakeholder relations, and concerns about algorithm transparency, accountability, and institutional trust. Existing research on AI implementation in fintech has focused largely on technology acceptance and system usability, leaving a gap in understanding transparency as a strategic issue of public relations (PR) in a cross-cultural context. Purpose: This paper aims to examine how cross-cultural PR practices can maintain institutional trust through algorithmic transparency and Explainable Artificial Intelligence (XAI) in the AI-driven fintech industry. Methods: This study employed a cross-cultural qualitative approach, involving 24 participants from Jakarta and Melbourne, consisting of fintech users, PR practitioners, and digital banking professionals. Data were collected through semi-structured interviews and analyzed thematically using Relationship Management Theory (RMT) and the Two-Way Symmetric Communication Model. Results: This study found that participants in Jakarta, representing a culture with a high Power Distance Index (PDI), prioritized institutional openness, accountability, and transparency as key determinants of trust. In contrast, participants in Melbourne endorsed user autonomy, efficiency, and functional performance. This study further demonstrates that XAI functions as a form of digitally-mediated symmetric communication that reduces information asymmetry and strengthens organizational legitimacy across cultural contexts. Conclusions: Algorithmic transparency has evolved beyond a technical feature to become a strategic communication mechanism that shapes institutional legitimacy and public trust in the AI-mediated fintech ecosystem. Implications: Theoretically, this study extends the RMT and the Two-Way Symmetric Communication Model to the context of AI-mediated communication. Practically, fintech organizations must integrate communication ethics and transparency into AI governance to maintain long-term stakeholder trust and organizational legitimacy.